Intrathecal Administration of Melatonin Ameliorates the Neuroinflammation- Mediated Sensory and Motor Dysfunction in A Rat Model of Compression Spinal Cord Injury - Fakhri, Sajad; Kiani, Amir; Jalili, Cyrus; Abbaszadeh, Fatemeh; Piri, Sana; Farzaei, Mohammad H.; Rastegari-Pouyani, Mohsen; Mohammadi-Noori, Ehsan; Khan, Haroon (Current Molecular Pharmacology, 2021)
Background: Spinal cord injury (SCI), often characterized by sensory-motor dysfunction, is a major debilitating disorder of the central nervous system. As no useful treatment for post- SCI complications has been approved thus far, finding novel treatments is of great importance. Objective: Considering the promising effects of melatonin (MEL) against destructive mechanisms in other models of brain damage, in the current study, we evaluated its ameliorative effects on sensory- motor outcomes, inflammatory mediators, histological changes and other post-SCI complications. Methods: Rats in SCI and MEL groups underwent laminectomy followed by a severe compression injury by an aneurysm clip. Then, intrathecal treatment with vehicle (5% dimethyl sulfoxide) or MEL was carried out post-injury. Acetone drop, von Frey, inclined plane, and BBB tests as well as weight changes and auricle temperature, were used to evaluate the neuropathic pain, motor function, and other post-SCI complications. The effects of MEL on the activity of MMP-2 and MMP-9 were assessed using the gelatin zymography method every week till day 28 post-SCI. Histopathological assessments were performed on days 14, 21, and 28. Results: MEL treatment resulted in decreased motor dysfunction, mechanical and cold allodynia, auricle temperature, and also ameliorated weight loss. Moreover, MEL suppressed MMP-9 activity while increasing that of MMP-2 post-SCI, indicating its anti-neuroinflammatory effects. Also, MEL significantly preserved white matter myelinated areas and the number of sensory neurons post-SCI. Conclusion: The results suggest MEL as a promising candidate for medical therapies with advantageous effects on improving functional recovery through suppressing inflammatory mediators, and attenuating spinal tissue damages.
Keywords: melatonin